Partially Coherent Optical Diffraction Tomography Toward Practical Cell Study - Soto, Juan M.; Rodrigo, José A.; Alieva, Tatiana (Frontiers in Physics, 2021)
Optical diffraction tomography (ODT) is a computational imaging technique based on refractive index (RI) contrast. Its application for microscopic imaging of weakly absorbing and scattering samples has been demonstrated by using a specially designed holographic microscope with angular scanning of the coherent sample illumination direction. Recently, an alternative low cost technique based on partially coherent sample illumination (PC-ODT) which is compatible with the conventional widefield transmission microscope has been established. In this case the 3D RI distribution of the sample is obtained by deconvolution from a single stack of through-focus intensity images. The performance of PC-ODT has been successfully tested on various fixed specimens (diatoms frustule and biological cells) and moving bacteria. Here, we demonstrate that the PC-ODT is an efficient tool for analysis of living eukaryotic cell dynamics at short and long term periods. The COS-7 cells, which hail from the African green monkey kidney, have been chosen for this study. A fast data acquisition setup comprising an optical scanning module can be easily attached to the microscope and it allows observing cell 3D organelle movements and RI variations with the required temporal resolution. In particular, a more rapid nucleoli rotation than previously reported has been found. The long term cell monitoring during necrosis reveals significant changes in cell dry mass concentration obtained from recovered RI contrast.